1944
DOI: 10.1192/bjp.90.378.410
|View full text |Cite
|
Sign up to set email alerts
|

Convulsion Therapy

Abstract: Therapeutic convulsions were introduced by Meduna (1937) in 1934. After preliminary trial with intramuscular camphorated oil, Meduna soon discovered the great advantages of intravenous cardiazol (leptazol, metrazol), which remains the best of the chemical methods of fit production. Many descriptions of the various aspects of the cardiazol fit are available (Cook, 1938a; Ebaugh and Shanahan, 1939; Katzenelbogenet al., 1939; Strauss, Landis and Hunt, 1939; Dean, 1940; Hemphill, 1940).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 145 publications
0
22
0
Order By: Relevance
“…Just as Cardiazol was being abandoned, studies by Bianchi and Chiarello, and by Cheney, showed superior results in catatonic states compared with ECT (Kalinowsky et al, 1946), suggesting that the undesirable aspects of Cardiazol -the fear and severity of fit -had therapeutic impact. As it was sometimes used to eradicate the 'faulty habits' of refractory cases (Cook, 1944), some patients may have been able to modify their behaviour to avoid further exposure. Henry Rollin reflected on Cardiazol as 'mediaeval torture' (Valentine, 1996: 80).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Just as Cardiazol was being abandoned, studies by Bianchi and Chiarello, and by Cheney, showed superior results in catatonic states compared with ECT (Kalinowsky et al, 1946), suggesting that the undesirable aspects of Cardiazol -the fear and severity of fit -had therapeutic impact. As it was sometimes used to eradicate the 'faulty habits' of refractory cases (Cook, 1944), some patients may have been able to modify their behaviour to avoid further exposure. Henry Rollin reflected on Cardiazol as 'mediaeval torture' (Valentine, 1996: 80).…”
Section: Resultsmentioning
confidence: 99%
“…Harris and Birnie (1938) at West Park found positive outcomes in stuporous cases whether schizophrenic or depressive. Convulsive therapy appeared particularly valuable in involutional melancholia, as, unlike the self-remitting tendency of other depressive disorders, sufferers commonly slid into perpetual gloom (Cook, 1944). Agitated suicidal cases could be promptly and effectively treated, thus reducing the burden of close surveillance.…”
Section: The True Value Revealedmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to earlier, m ainly psychoanalytic, theorising about the psychological impact of ECT. Psychogenic theories of ECT' s action were summ arised in a review article by Cook (1944). Earlier belief in the therapeutic effects of fear had been largely replaced by theories about the healing nature of this sym bolic death and re-birth.…”
Section: Introductionmentioning
confidence: 99%